THE EFFECT OF CAPITAL STRUCTURE, PROFITABILITY, FIRM SIZE AND FIRM RISK ON FIRM VALUE - Trisandi Eka Putri; Asri Lestari (JASS (Journal of Accounting for Sustainable Society), 2023)
The purpose of this study was to determine the effect of capital structure, profitability, firm size and firm risk on firm value in food and beverage sub-sector companies listed on the malaysia stock exchange. There are 4 independent variables in this study including, capital structure measured using Debt to Equity Ratio (DER), profitability using Return on Investment (ROI) measurement, company size using SIZE and company risk using RISK. While the dependent variable of this research is firm value with Price Book Value (PBV) measurement. This study uses data from the financial statements of 15 companies for 5 years from 2016-2020 using purposive sampling technique. The data analysis technique used in this study was multiple regression analysis with the help of the SPSS application. The results of this study indicate that the variables of capital structure and firm risk have a positive effect on firm value, while profitability and firm size have no effect on firm value.